IFC Annual Report 2021 : Meeting the Moment - International Finance Corporation (International Finance Corporation, Washington, DC, 2021)
International Finance Corporation (IFC), a member of the World Bank Group, is the largest global development institution focused on the private sector in emerging markets and developing economies. We work in more than 100 countries, using our capital, expertise, and influence to create markets and opportunities for better lives. In fiscal year 2021, we invested $31.5 billion in total commitments, including $23.3 billion in long-term finance and $8.2 billion in short-term finance, to private companies and financial institutions in emerging and developing economies, leveraging the power of the private sector to end extreme poverty and boost shared prosperity. For more information, visit www.ifc.org.